PRO-APOPTOTIC EFFECTS OF APPLE PROCYANIDINS IN HUMAN COLON CANCER CELLS AND THEIR DERIVED METASTATIC CELLS - María E. MALDONADO C. (Universidad de Antioquia, 2010)
Apples are a rich source of Procyanidins (Pcy) which are able to inhibit colon carcinogenesis in animal models, but the mechanisms through which this occurs are not well understood.The evidence obtained in our laboratory and by other researchers, which shows that Pcy trigger apoptosis through different mechanisms in human colon adenocarcinoma SW480 cells and their derived metastatic SW620 cells is reviewed in this paper. In the apoptosis induced by Pcy, the polyamine metabolism is involved, but it is not present in SW480 cells. There is a differential sensitivity of both cells lines to the activation of TRAIL-death receptors. Pcy enhance the sensitivity of SW480 cells to TRAIL by activating the extrinsic apoptotic pathway, and overcome TRAIL-resistance in SW620 cells involving a cross-talk between the extrinsic and intrinsic pathways; and a Pcy-induced ROS production favoring mitochondria disruption. In addition, Pcy activate Fas receptor in SW480 cells, whereas SW620 cells are Fas-resistant despite the up-regulated Fas expression. Surprisingly, activation of the Fas receptor-mediated apoptosis by Pcy is observed in SW620 cells after inactivation of TRAIL-death receptors, suggesting that Fas-resistant phenotype may be associated with alterations in downstream events between TRAIL-death and Fas receptors. These data highlight the potential interest of apple Pcy in colon cancer prevention and therapy (combination therapy).